Development and validation of an RP-HPLC method for the simultaneous determination of Escitalopram Oxalate and Clonazepam in bulk and its pharmaceutical formulations - Bhimanadhuni, Chusena Narasimharaju; Garikapati, Devala Rao; Usha, Pasupuleti (International Current Pharmaceutical Journal, 2012)
A Simple, efficient and reproducible reverse phase high performance liquid chromatographic method was developed and validated for the Simultaneous determination of Escitalopram oxalate and Clonazepam in combined dosage form. The separation was effected on a Hypersil ODS C18 column (250mm X 4.6mm; 5µ) using a mobile phase mixture of buffer and acetonitrile in a ratio of 50:50 v/v at a flow rate of 1.0ml/min. The detection was made at 240nm. The retention time of Escitalopram oxalate and Clonazepam was found to be 2.840± 0.007min and 4.007±0.006 min. Calibration curve was linear over the concentration range of 20-120µg/ml and 1-6µg/ml for Escitalopram oxalate and Clonazepam. All the analytical validation parameters were determined and found in the limit as per ICH guidelines, which indicates the validity of the method. The developed method is also found to be precise, accurate, specific, robust and rapid for the simultaneous determination of Escitalopram oxalate and Clonazepam in tablet dosage forms. DOI: http://dx.doi.org/10.3329/icpj.v1i8.11249 International Current Pharmaceutical Journal 2012, 1(8): 193-198